Olfactory Neuroblastoma: Surgical Treatment Experience of 42 Cases - Cai, Xiao; Peng, Zhouying; Zhang, Hua; Fan, Ruohao; Fang, Yan; Xie, Zhihai (Frontiers in Surgery, 2022)
Objective Our purpose was to estimate the safety and effectiveness of the endoscopic endonasal approach (EEA) in olfactory neuroblastoma (ONB) and determine whether preservation of the dura and olfactory bulb could be considered in selected patients. Methods We retrospectively reviewed patients diagnosed with ONBs between July 2010 and June 2021 at our institution, and collected data on demographic, disease stage, surgical approach, overall survival (OS), disease-free survival (DFS), and postoperative complications. Results The study sample included 42 patients (8 treated for recurrence and 34 initial cases), 28 of which were men and 14 were women with a median age of 47.19 years. The mean duration from the beginning of treatment and follow-up time was 8.91 and 51 months, respectively. Among the 42 patients, 32 had unilateral lesions, and the rest had bilateral lesions. Patient symptoms were predominantly nasal, and four patients presented without any symptoms. The modified Kadish staging was A in three patients, B in 14 patients, C in 17 patients, and D in 8 patients. According to the preoperative examinations, five patients had cervical lymph node metastasis, and no patients had distant metastases. EEA was used in 38 patients, cranioendoscopic approach in 3, and open craniofacial approach in 1. The 5-year OS and DFS rates were 89.1 and 79.2%, respectively. The 2-year OS and DFS rates were both 89.1%. The overall surgical complication incidence was 9.52% (one cerebrospinal fluid rhinorrhea, one cervical hematoma, and two epileptic seizures). Conclusion The present results support the importance of earlier treatment for advanced ONB and the fact that it is safe and efficacious to treat ONBs via EEA. The preservation of the dura can be considered for select patients—specifically those without skull base involvement and who underwent postoperative comprehensive therapy.